Natural disasters and human mobility - Linguère Mously Mbaye; Klaus F. Zimmermann (University of Bonn, Center for Development Research (ZEF), 2016)
This paper reviews the effect of natural disasters on human mobility or migration. Although there is an increase of natural disasters and migration recently and more patterns to observe, the relationship remains complex. While some authors find that disasters increase migration, others show that they have only a marginal or no effect or are even negative. Human mobility appears to be an insurance mechanism against environmental shocks and there are different transmission channels which can explain the relationship between natural disasters and migration. Moreover, migrants' remittances help to decrease households' vulnerability to shocks but also dampen their adverse effects. The paper provides a discussion of policy implications and potential future research avenues.
Keywords: J61; O15; Q54; Q56; 330; natural disasters; forced migration; channels; remittances; migration as insurance; floods; earthquakes; droughts